Transition-metal-catalyzed reactions involving arynes - Dhokale, Ranjeet A.; Mhaske, Santosh B. (Synthesis-Stuttgart, 2018)
The plethora of transformations attainable by the transition-metal-catalyzed reactions of arynes has found immense contemporary interest in the scientific community. This review highlights the scope and importance of transition-metal-catalyzed aryne reactions in the field of synthetic organic chemistry reported to date. It covers transformations achieved by the combination of arynes and various transition metals, which provide a facile access to a biaryl motif, fused polycyclic aromatic compounds, different novel carbocycles, various heterocycles, and complex natural products. 1 Introduction 2 Insertion of Arynes 3 Annulation of Arynes 4 Cycloaddition of Arynes 5 Multicomponent Reactions of Arynes 6 Miscellaneous Reactions of Arynes 7 Total Synthesis of Natural Products Using Arynes 8 Conclusion
Keywords: annulation; arynes; Cycloaddition; Insertion; multicomponent; Natural products; Transition Metal

Rapid synthesis of zwitterionic phosphonium benzoates by a three-component coupling involving phosphines, arynes and CO2 - Bhattacharjee, Subrata; Raju, Anjali; Gaykar, Rahul N.; Gonnade, Rajesh G.; Roy, Tony; Biju, Akkattu T. (Chemistry-An Asian Journal, 2020)
A mild and easy to perform multicomponent coupling involving phosphines, arynes generated from 2-(trimethylsilyl)aryl triflates, and CO(2)allowing the transition-metal-free synthesis of zwitterionic phosphonium benzoates has been developed. The reaction proceeds via the generation of 1 : 1 zwitterionic intermediates from phosphines and arynes followed by the interception with CO(2)to deliver the carboxylates in moderate to good yields instead of the anticipated benzooxaphosphol-3(1H)-ones.
Keywords: arynes; Carbon dioxide; multicomponent coupling; Phosphines; zwitterions